(untitled) (European Journal of Formal Sciences and Engineering, 2020)
Using computational fluid dynamics (CFD) in agriculture field especially in designing greenhouses is becoming ever more important to reduce the energy consumption, wherefore a comparison between the experimental and numerical results increasing the credibility of theoretical studies and therefore depending on it. Forced ventilation greenhouse has been used in even span greenhouse to study the experimental measurements of temperature distribution in summer rush hours, the experiment has been performed in October 6 University, Giza, Egypt. More than one turbulence models (Standard K-?, RNG K- ?, Reynolds Stress Model (RSM), Transition Shear-Stress Transport (SST), Standard K-? and K-KL-?) are used for the (CFD) numerical study implemented for comparison between the experimental and numerical measurements. After this study can get that SST turbulence model is the most efficient numerical solution for this case, a good qualitative and quantitative agreement found between the numerical results and the experimental measurements.